Innovative Multi-Degradation Rigs: Fast-Tracking Material Validation for Resilient Offshore Renewable Energy (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The MORE project (Next Generation Marine Materials for Resilient Offshore Renewable Energy Devices) focuses on addressing multi-degradation challenges in offshore renewable energy (ORE) devices through the development of an advanced methodology for material selection and validation. Offshore environments subject critical ORE components to simultaneous wear, corrosion, and fatigue, leading to multi-degradation, which is a primary cause of unexpected failure. This paper presents the initial results of the MORE work about two complementary test rigs designed for multi-degradation analysis: a small-scale multi-degradation (SSMD) rig and a laboratory-scale multi-degradation (LSMD) pilot test rig. Two SSMD rigs provide a controlled environment for simulating and isolating the fundamental mechanisms of tribocorrosion and fatigue at the micro-scale, facilitating rapid, low-cost material screening. In contrast, the LSMD rig replicates real-world offshore conditions to validate the scalability and industrial applicability of materials previously tested at small-scale. The MORE project’s integrated approach to multi-degradation testing represents a significant advancement over conventional qualification methods by offering a faster, more reliable pathway for material validation. By harmonizing small- and large-scale testing, MORE aims to deliver a validated, scalable methodology for predicting the long-term behavior of critical ORE components, contributing to the advancement of resilient renewable energy systems. The project’s ongoing work will culminate in the creation of industry guidelines and recommended practices, ensuring broad adoption by developers, manufacturers, and policymakers in the offshore energy sector.